India's Lust for 'Luxe' : A study of consumer perceptions - Soni, Saloni (2009)
India leads the world in wealth creation (Voight, 2007). The country’s economy is constantly growing at a rate of 7-8% each year and High Net Worth Individuals are on a rise. This makes India a lucrative and beneficial market for luxury brand goods. Analysts are predicting that over the next decade, India could become luxury's biggest market. As a result, it was important to conduct this research. The main purpose of this study is to find out the characteristics that encourage people buy luxury brands and the factors that influence their decisions.